Synthesis of β-Ga2O3 thin film assisted by microwave annealing - Nafiseh Badiei (AIP Advances, 2022)
β-Ga2O3 is increasingly being used in power electronics and UV sensors. The preparation of β-Ga2O3 thin films requires costly and time-consuming fabrication processes. Therefore, developing short-time and low-cost fabrication processes of the β-Ga2O3 thin film has been greatly demanded to quicken the pace of applying this material in practical devices and systems. In this paper, a new fabrication process combining physical vapor deposition and microwave localized annealing has been postulated for β-Ga2O3 thin films. The experimental results show that after microwave annealing band gaps have been slightly adjusted, the surface morphology has been improved and extra diffraction peaks appear, which give rise to stronger β-phase characteristics in the Ga2O3 thin film. Calculation based on density functional theory has been conducted to show the electronic band structures, formation energies, and optical absorptions of both types.